Pseudocapacitive reaction enhanced porous Co0.85Se/N-doped carbon anodes for advanced sodium-ion battery with high rate and capacity. (20th October 2019) - Liu, Mengting; Jing, Panpan; Wang, Ting; Hou, Xiaoyi; Liu, Michael; Sun, Zifei; Li, Junshuai; He, Deyan
Abstract: Sodium-ion batteries (SIBs) have attracted extensive interests for the large electronic equipment. Increased size of the Na-ion is the primary factor of its slow diffusion in the bulk, which poses big challenges for the manufacturing of active materials suitable for SIBs. Here, we present a set of porous Co0.85 Se/N-doped carbon (Co0.85 Se/NC) composites with an excellent ratio (above 85%) of surface/near-surface pseudocapacitance Na-ion phenomena. When cycled at 100 mA g −1, the Co0.85 Se/NC-1.0 anode delivers an ultrahigh initial discharge capacity of 713 mAh g −1 . During the 100 cycles under 1000 mA g −1, its reversible specific capacity is up to 509 mAh g −1 . Besides, the anode also presents a robust rate performance with a limited capacity loss between 100 and 5000 mA g −1 . Especially, a capacity of 382.8 mAh g −1 is still delivered at 5000 mA g −1 . Among the various cobalt selenide-based materials, such an outstanding Na + storage capacity and rate performance contribute the Co0.85 Se/NC composites to be a promising candidate of SIBs. Graphical abstract: Image 100288